ANALISIS SUSTAINABLE PRODUCT INNOVATION SEBAGAI BASIS COMPETITIVE ADVANTAGE PADA PRODUK ECOPRINT ANDCRAFT SURABAYA - Icha Rohmatul Jannah; Devinta Nur Arumsari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The high environmental impact of the fashion industry, driven by chemical use, textile waste, and fast fashion production patterns, underscores the need to develop more sustainable products through innovation grounded in the dimensions of planet, people, and profit. This study aims to analyze the implementation of Sustainable Product Innovation in the development of ecoprint products at ANDCraft Surabaya and its role in establishing Competitive Advantage. This study employed a descriptive qualitative approach through non-participant observation, in-depth interviews with the two founders of ANDCraft and loyal customers, and documentation. Informants were selected using purposive sampling supported by snowball sampling, in which loyal customers were accessed through recommendations from the ANDCraft owners and then verified based on the research criteria. The results indicate that Sustainable Product Innovation has been implemented through the use of natural materials, environmentally friendly production processes, waste management practices reflecting circular principles, as well as design innovation and product diversification. In addition, innovation is reflected in the social dimension through education and collaboration, and in the profit dimension through value creation and cost efficiency. The implementation has proven to contribute to Competitive Advantage through product differentiation, strengthening of eco-fashion brand image, and increased customer trust, although challenges remain in digital marketing optimization and sustainability communication. This study highlights the importance of integrating product innovation, marketing strategies, and sustainability communication to support sustainable business competitiveness.